Peran Guru Dalam Mendukung Kemandirian Belajar Siswa Tuna Rungu di SLB Ayodya Tulada Surabaya - May widiyani, Irene; Harsiwi, Nova Estu (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
Independent learning is important for deaf students. This research aims to examine the role of teachers in supporting the independent learning of deaf students at SLB Ayodya Tulada Surabaya. A case study approach was used to collect data through observation, interviews with teachers and students, as well as documentation of teaching and learning activities. The research results show that teachers act as facilitators, motivators, mentors and evaluators in supporting the independent learning of deaf students. Teachers facilitate learning by using various methods and media that suit the needs of deaf students. Teachers also motivate students to learn independently, and guide them in developing effective learning skills. In addition, teachers evaluate student learning progress and provide feedback for improvement.